NPK combinations mitigate the deleterious effects of salt stress on the morphophysiology of West Indian Cherry - Silva Filho, Antonio Manoel da; Costa, Thamara Silva da; Melo, Alberto Soares de; Costa, Denis Soares; Silva, André Alisson Rodrigues da; Gheyi, Hans Raj; Silva, Francisco de Assis da; Dias, Mirandy dos Santos (Comunicata Scientiae, 2023)
Under salt stress, plant growth and development are negatively affected due to physiological changes, requiring strategies such as fertilization management to minimize these effects. In this scenario, this study aimed to evaluate the effect of combinations of nitrogen, phosphorus, and potassium on the growth, leaf water status, electrolyte leakage, and gas exchange of West Indian Cherry grown under water stress in the second year of production. The experiment was conducted in a protected environment in Campina Grande - PB. The treatments were distributed in a randomized block design with a 2 × 10 factorial arrangement with three replications corresponding to two electrical conductivity levels of irrigation water– ECw (0.6 and 4.0 dS m-1) and ten combinations of fertilization with nitrogen, phosphorus, and potassium (80-100-100; 100-100-100; 120- 100-100; 140-100-100; 100-80-100; 100-120-100; 100-140-100; 100-100-80; 100-100-120, and 100-100-140% of the recommendation in the second year of production). Irrigation with the ECw of 4.0 dS m-1 negatively affected plant growth, the leaf water status, electrolyte leakage, and the leaf gas exchange of West Indian Cherry. However, the 40% increase (C4 -140-100-100% of the recommended N-P2O5-K2O level) in the nitrogen level mitigated the deleterious effects of salt stress on the relative water content, internal CO2 concentration, and the CO2 assimilation rate of West Indian Cherry plants in the second year of production.